1993
DOI: 10.1007/bf01401124
|View full text |Cite
|
Sign up to set email alerts
|

Multiple intracranial aneurysms: Surgical treatment and outcome

Abstract: We report a series of 41 patients with multiple intracranial aneurysms, analyzing them by type of surgical treatment and prognosis. We compare our findings with those of the largest published series and draw conclusions regarding the most appropriate treatment. The upshot would seem to be that morbidity and mortality depend chiefly on whether the aneurysms are bilateral or unilateral and on the patient's pre-operative status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Therefore, treatment should be initiated as soon as possible in hemorrhaging patients 19,20. In order to treat bleeding MirAn, the initial treatment should focus primarily on the hemisphere with the bleeding aneurysm 17,21,22. Our findings suggested that the rupture risk was significantly higher for large aneurysms, which is consistent with the findings of previous studies 11,23.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, treatment should be initiated as soon as possible in hemorrhaging patients 19,20. In order to treat bleeding MirAn, the initial treatment should focus primarily on the hemisphere with the bleeding aneurysm 17,21,22. Our findings suggested that the rupture risk was significantly higher for large aneurysms, which is consistent with the findings of previous studies 11,23.…”
Section: Discussionsupporting
confidence: 89%
“…4,5,26 Surgical clipping of all aneurysms can be performed in one session in 70 to 80% of patients with multiple intracranial aneurysms. 2,5,26,31,38 A unilateral location of multiple intracranial aneurysms in the anterior circulation is more favorable for a one-stage procedure than one involving the bilateral anterior circulation or a combination of anterior and posterior circulation. 25,31,38 The onestage procedure can be performed using a unilateral, a contralateral, or a bilateral surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] In patients with multiple aneurysms that cannot be clipped in one surgical session, rapid, accurate identification of the ruptured aneurysm is important. 14,15 Inaccurate determination of the site of the ruptured aneurysm may result in clipping of the wrong aneurysm. It has been reported that postoperative re-bleeding is usually due to a misinterpretation of the location of the ruptured aneurysm in the presence of multiple aneurysms.…”
Section: Jssn 2018; 21 (1)mentioning
confidence: 99%